The concise AACR2 - Gorman, Michael, 1941- (American Library Association ; Canadian Library Association ; Chartered Institute of Library and Information Professionals, 2004)
Michael Gorman, co-editor of the original AACR2, explains the more generally applicable AACR2 rules for cataloging library materials in simplified terms that make the rules more accessible and practical for practitioners and students who are in less complex library and bibliographic environments.